Nucleic Acid Amplification Strategies for Biosensing, Bioimaging and Biomedicine - Zhang, Shusheng; Bi, Sai.; Song, Xinyue; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book describes the rational design, development and application of nucleic acid amplification strategies for biosensing, bioimaging and biomedicine. It consists of fifteen chapters demonstrating the use of these strategies in various areas, including fluorescence techniques, Chemiluminescence biosensors, electrochemiluminescence biosensors, colorimetric assays, surface plasmon resonance technologies, electrochemical DNA sensors, photoelectrochemical biosensor, nanopore sensors, quartz crystal microbalance, fluorescence imaging, surface-enhanced Raman spectroscopy, in vitro and in vivo metal ions detection, theranostics and microdroplet chips. Offering a collection of reviews illustrating the latest advances in biochemical analysis and therapeutics, the book shares valuable insights into current challenges and future prospects, making it a valuable resource for a wide readership in the various fields of biosensing, bioimaging and biomedicine.
Introduction -- Nucleic Acid Amplification Strategies-Based Chemiluminescence Biosensors -- Nucleic Acid Amplification Strategies-Based Electrochemiluminescence Detection -- The Application of Nucleic Acid Amplification Strategies in Photoelectrochemistry Technologies -- Nucleic Acid Amplification Strategies: Rational Design and Electrochemical Signaling -- Nucleic Acid Amplification Strategies-Based Nanopore Sensors -- DNA Amplification Strategies Based on QCM -- Nucleic Acid Amplification Strategies in Surface Plasmon Resonance Technologies -- The Application of Nucleic Acid Amplification Strategies in the Raman Spectra Technologies -- The Application of Nucleic Acid Amplification Strategies in the Single Molecule Detection -- The Application of Nucleic Acid Amplification Strategies in the Environmental Detection -- Fluorescence Techniques Based on Nucleic Acid Amplification Strategies: Rational Design and Application -- Nucleic Acid Amplification Strategies for in Vitro and in Vivo Imaging -- The Application of Nucleic Acid Amplification Strategies in Theranostics.
Keywords: Analytical chemistry; Biomaterials; Nucleic acids; Biotechnology; Physical chemistry; Analytical Chemistry; Nucleic Acid; Biotechnology; Physical Chemistry